Bridging Islamic Financial and Socio-Scientific Literacy: Zakat as a Tool for Environmental Education - Syafriyon; Rusdi; Mursal (Jurnal Penelitian Pendidikan IPA, 2026)
This qualitative case study examines how the integration of Islamic financial literacy and socio-scientific literacy transforms zakat-paying behaviour among parents of elementary school students and positions zakat as a sustainable financing tool for environmental education. Situated within the SDIT Adzkia educational ecosystem in Padang, West Sumatra, Indonesia, the study draws on semi-structured interviews, participant observation, and document analysis involving school principals, zakat institution managers, committee members, and parents across three consecutive Ramadhan periods. Findings reveal that prior to structured literacy interventions, institutional zakat collection remained marginal at 0.72 per cent of potential. Following the systematic deployment of integrated literacy programmes combining Islamic financial education with socio-scientific framing of environmental stewardship, collection surged to 5.33 per cent, representing a 7.4-fold increase. The study demonstrates that bridging these two literacy domains creates a synergistic motivational framework in which zakat transcends conventional poverty alleviation to function as a community-driven instrument funding eco-literacy programmes and student-led green initiatives. These findings contribute to the intersection of Islamic philanthropy, science education, and environmental sustainability, offering an evidence-based model for aligning zakat resources with Education for Sustainable Development at the elementary level.